STUDI TENTANG TENUNAN PANDAI SIKEK DI RUMAH TENUN PUSAKOKECAMATAN X KOTOKABUPATEN TANAH DATAR - Meyliona, Geby; Adriani, Adriani; Nelmira, Weni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
CleverweavingSikekproducthas undergonemany changesincludingin terms ofcolors and patternsareused, resulting in the erosion ofcultural values​​containedinwovensongket. CleverweavingSikekonethat still retainsits originalshapeisPusakoWeavingHouse. The purposeof this studyistodescribe themotifwovensongketSikekClever, meaningmotif, weavingtechniquesandtypes ofproductson the HomeWeavingPusako. The method usedin this studyis aqualitativemethod. Typesof datain the form ofprimary and secondary data. Techniques ofdata collectionthrough observations, interviewsanddocumentation. Techniquesof dataanalysiswas done by usingan interactivemodel ofanalysisrelating to thesubject matterthat isthemodel ofdata reduction, data presentation, and conclusion. The results showedwovenmotifPusakoWeavingCleverHomesSikekderivedfromflora(plants), fauna(animals) andother objects. WeavingwovenmotifPusakoCleverHomesSikekthere are 35types. Eachmotifhas adifferent meaning. Meaning ofthemotifin the form ofdeliveringcustommessages, bothdoctrineandproceduresandcustomarylegal orderis the referenceorpegangganMinangpeoplelivingin daily life. WovensongketweavingtechniquesonPusakoWeavingCleverHomesSikekinitially isprovidingKasali, Turak, pancukiaandpalapah. After that juststartedweaving. The products producedby the HouseWeavingCleverPusakoSikekiscompletethe formsalendangcustom clothing, gloves, cawek, sisamping, tangkuluakandsaluak. Kata Kunci: Tenunan, motif, makna motif, teknik menenun, jenis produk, Rumah Tenun Pusako